The Practice of Profitability and Liquidity of Nepalese Joint Venture Banks: A Comparative Study - Manoj Kumar Chaudhary, Ajay Prasad Dhakal, Madhav Adhikari (International Journal of Modern Agriculture, 2021)
The paper aims to describe the relationship between profitability and liquidity of Nepalese joint venture banks. The descriptive research design has been used to examine the relationship. In Nepal, a total of 27commercial bans including 7 joint ventures, 20 developments banks and 22 finance companies in operation in this study period of time. Out of 7 Joint venture banks, Everest bank limited and Himalayan bank limited were selected purposively to describe and compare its practice and relationship. The results reveled that a positive relationship exit between profitability and liquidity in both joint venture banks. Therefore, the study conclude that the liquidity status of both banks plays a key role in banking performance of Nepalese banking Context.